Geotourism and geoparks as gateways to socio-cultural sustainability in Qeshm rural areas, Iran - Torabi Farsani, Neda (2019)
Cultural sustainability is the concept for the recovery and protection of cultural identities. It is linked to previous traditional practices through celebrating local and regional histories and passing down cultural values to future generations. Nowaday, geoparks as an innovation for the protection of natural and geological heritage play an important role in cultural sustainability in rural areas. Moreover, a geopark stimulates local socioeconomic and socio-cultural development by attracting an increasing numbers of visitors. The aim of this paper is to assess innovative strategies of geoparks for socio-cultural sustainability. To this end, electronic questionnaires were sent to all geoparks around the world (64) registered by UNESCO and just 25 questionnaire responses were received (20 in Europe and three in Asia (Malaysia, Japan and Iran), one in Australia, and one in South America (Brazil)). Additionally, the interview method was used to consider the role played by the creation of Qeshm geopark in reducing the negative cultural impacts of tourism in rural areas. Based on the results of the descriptive analysis, geopark activities promote cultural components in their territory.